PENILAIAN KETERAMPILAN PORTOFOLIO DALAM PEMBELAJARAN DI SEKOLAH - Supriani Supriani; Ubabuddin (CV. ADIBA AISHA AMIRA, 2023)
Portfolio assessment is a continuous assessment based on a collection of information that shows the development of students' abilities in a certain period. This information can be in the form of students' work from the learning process that is considered the best by students. In the portfolio assessment contains important things, namely the collection (storing), selection (sorting) and determination (dating), of a task (task). This Portfolio Assessment also has many benefits, objectives, assessment steps, methods of assessment and advantages and disadvantages.